Enhancing the photocatalytic activity of Cd–ZnS(EN)0.5 hybrid sheets for the H2 production. (6th November 2020) - Ramírez-Ortega, David; Ramos, Ana B.; Hernández-Gordillo, Agileo; Zanella, Rodolfo; Rodil, Sandra E.
Abstract: Ultrathin sheets of ZnS(EN)0.5 modified with Cd 2+ ions were prepared by chemical precipitation in a mixture of butanol-ethylenediamine-water solution. The Cd 2+ content was varied from 0.1 to 0.6 M ratio and its influence in the physicochemical properties of the formed Cd–ZnS(EN)0.5 hybrid compounds was investigated by diverse techniques: X-ray Diffraction, Thermogravimetric, Textural analysis, Infrared, Diffuse Reflectance and X-ray Photoelectron Spectroscopies, Scanning Electron and High-Resolution Transmission Electron Microscopy. The photocatalytic H2 production of the unmodified ZnS(EN)0.5 hybrid was tested using hydrazine, ethanol, and methanol as sacrificial electron donors reagents ( SEDr ), presenting an H2 evolution rate of 2.4, 21 and 23 μmolh −1, respectively. The results showed that the orthorhombic ZnS(EN)0.5 structure was stable but suffer exfoliation of the lamellar structure during the photocatalytic cycles in methanol-water solution under UV irradiation. The doped Cd–ZnS(EN)0.5 hybrid presented an enhanced H2 production rate (32 μmolh −1 ) for low Cd 2+ doping, showing only minor exfoliation of the lamellar structure and stability of the orthorhombic structure, preserving the high photoactivity after 6 cycles of irradiation. Graphical abstract: Image 1 Highlights: Doped Cd–ZnS(EN)0.5 hybrid were prepared in mixture protic solvent. Hydroxylated surface of sheets ZnS(EN)0.5 and Cd–ZnS(EN)0.5 were obtained. High H2 evolution rate was achieved with Cd–ZnS(EN)0.5 at 0.1 mol% of Cd contents. Exfoliation process in both lamellar materials induce to increase the photoactivity.